2022
DOI: 10.1152/japplphysiol.00283.2021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of −10° and −30° head-down tilt on cerebral blood velocity, dynamic cerebral autoregulation, and noninvasively estimated intracranial pressure

Abstract: Background: Steady-state cerebral blood flow (CBF) and dynamic cerebral autoregulation are reportedly maintained during -10° head-down tilt (HDT) despite slight increases in intracranial pressure (ICP). However, the higher ICP during -30° HDT may alter steady-state CBF and dynamic cerebral autoregulation. The present study hypothesized that steady-state CBF and dynamic cerebral autoregulation would be altered by higher ICP during -30° HDT than during 0° and -10° HDT. Methods: Seventeen healthy participants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…We found that the facial SBF in the cheek decreased as the angle of HDT became steeper. In contrast, no difference has been recognized in cerebral blood flow velocity among three trials in our previous report (Kato et al., 2022). Alterations in the intra‐ and extracranial circulation are thus suggested to differ during HDT.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…We found that the facial SBF in the cheek decreased as the angle of HDT became steeper. In contrast, no difference has been recognized in cerebral blood flow velocity among three trials in our previous report (Kato et al., 2022). Alterations in the intra‐ and extracranial circulation are thus suggested to differ during HDT.…”
Section: Discussionmentioning
confidence: 55%
“…in cerebral blood flow velocity among three trials in our previous report (Kato et al, 2022). Alterations in the intra-and extracranial circulation are thus suggested to differ during HDT.…”
Section: Cheek Sbf and Extracranial Circulationmentioning
confidence: 52%
See 2 more Smart Citations
“…Non‐invasive cerebral perfusion pressure (nCPP) was also calculated by subtracting nICP from MAP MCA . Cerebrovascular resistance index (CVRi) was calculated as nCPP divided by the 6‐min average of MCAv (Kato et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%